2021
DOI: 10.1088/2053-1591/ac0a00
|View full text |Cite
|
Sign up to set email alerts
|

The experimental analysis of creep and corrosion properties of polymeric tube reinforced by glass, carbon and Kevlar fibers

Abstract: Polymeric tubes, including epoxy and reinforcing fibers, are widely used in the petroleum and aerospace industries due to their high strength and corrosion resistance. In this study, corrosion and creep properties of resin-based tubes reinforced by Glass fibers (GFR), Carbon fibers (CFR), and Kevlar fibers (KFR) were investigated using tubes made by using a 45-degree unilateral winding method. The highest creep strain was obtained for the CFR equal to 0.7445 and the lowest was obtained for KFR with the Kevlar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…al. [18] Examined the corrosion and creep characteristics of an epoxy-based composite material reinforced with Kevlar, carbon, and glass fibers. Results revealed that carbon fiber had the highest creep resistance in comparison with Kevlar and glass fibers, in contrast, Kevlar fiber exhibits the lowest corrosion risk among the three types of fibers.…”
Section: Introductionmentioning
confidence: 99%
“…al. [18] Examined the corrosion and creep characteristics of an epoxy-based composite material reinforced with Kevlar, carbon, and glass fibers. Results revealed that carbon fiber had the highest creep resistance in comparison with Kevlar and glass fibers, in contrast, Kevlar fiber exhibits the lowest corrosion risk among the three types of fibers.…”
Section: Introductionmentioning
confidence: 99%